Factors associated with immunisation coverage of children aged 12-24 months in Erbil / Iraq 2017-2018 - Hassan, Zahraa Ahmed; Ahmed, ohammed Jasim (International Journal of Psychosocial Rehabilitation, 2020)
This study evaluated immunization-related factors in 520 children there age are between 12- 24 months in the year 2017-2018 at Erbil city in Iraq. Complex cluster sampling was used in this cross-sectional population household survey. Furthermore, Children who are not immunized on time are likely to be from family of low socio-economic status and having low parental educational level. In this study, the immunization coverage was assessed and the factors that affect immunization of children during the first year of life in Erbil were identified. Sexual and class factors have placed hurdles in total immunization, and thus the need for policies to address these inequalities are recommended.